Harmonising Faith and Tradition: Sacred Vocal Polyphony in Contemporary South African Christian Worship - Sakhiseni Joseph Yende (E-Journal of Humanities, Arts and Social Sciences)
This study aims to shed light on the intricate relationship between sacred vocal polyphony and the changing landscape of contemporary church music in South Africa. Anchored in a postcolonial theoretical framework, it sought to unravel the historical, cultural, and theological dimensions that underlie this fusion. The research was motivated by a dual purpose: to uncover the profound cultural intersections in South African worship practices and to address the existing gaps in scholarly discourse. Four central research questions, each delving into a specific facet of sacred vocal polyphony: its historical evolution within the South African church music context, its cultural and theological significance, its role in enhancing diversity and inclusivity in worship, and the challenges and opportunities in preserving its authenticity amidst contemporary influences, guided this inquiry. Through the qualitative method under critical discourse analysis, the study unveiled a rich tapestry of themes. These encompass the synthesis of indigenous rhythms with European harmonies, the theological depth embedded in polyphonic expressions, the empowerment of congregations through vocal diversity, and nuanced negotiations required to preserve authenticity. This research not only advances the understanding of how musical traditions intersect with cultural and religious identities but also sheds light on the resilience and adaptability of sacred music in South African worship. It serves as a valuable resource for scholars and practitioners in ethnomusicology, theology, and cultural studies, offering insights into the transformative potential of sacred vocal polyphony within the diverse tapestry of contemporary South African worship.